A Hybrid Algorithm For Optimal PMU Placement - Baba, M. (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper presents a hybrid approach envision to determine the optimal PMU placement problem (OPPP) in any sort of IEEE network to make it observable. While using the old version of Graph-Theoretic Procedure (GTH) for optimization purposes, it takes additional time to complete the process and uses an extra number of PMUs for the placement model. Therefore, the importance of the presented work is to improve the performance of GTH using a merging process, and a certain number of important parameters from the Recursive algorithm (RA) are combined successfully. The proposed work is tested on different IEEE-case systems such as IEEE-9, -14, -24, -30, and New England 39-case system. Moreover, the results of the proposed hybrid approach are compared with the existing techniques to get the effectiveness of the proposed work about minimizing the number of PMUs. Â© 2021 IEEE.